The Writing of Epidemic Through the Lens of Postmodernist Thought - Mahdeb , Aissa; Mouloudj, Rym (El Omda in Linguistics and Discourse Analysis, 2022)
Inspired by the postmodern wave, a so-called “epidemic” form of writing seeks to engage in reflection on fundamental questions primarily concerning the meaning of existence, faith, death, survival, and other issues related to our relationship with the world in which we live. It does not hesitate to question the processes and mechanisms of globalization and modernist logic, which are often considered to be the source of major contemporary problems.